IMPLEMENTASI PENDEKATAN BERORIENTASI OBJEK TERPADU UNTUK PENGEMBANGAN SISTEM INFORMASI YANG TERINTEGRASI PADA PT. SAPTA KARYA - Yovita A. Maria; Mohammad Fajar; Afifah (STMIK KHARISMA Makassar, 2020)
The aim of this study is to analyze and design a sales information system using a unified approach at PT. Sapta Karya. Literature studies, observations, and interviews are performed to define specifications of the system. In the analysis phase, activity diagrams is used to model business processes of the system, use case diagrams to define functional specifications, and sequence diagrams to specify interactions between sales, warehouse, and finance departments, and class diagrams are used to establish the static structure of the system which consists of a number of entities, such as Customers, Employees, Goods, and Transactions. In the design phase, the types of attributes and methods of the class diagram are defined, and activity diagrams for modeling the application logic. The unified approach in the development of an integrated system can be applied, where each division performs its own function and communicates through data exchange between them. The designed class diagrams can be used to map the database structure and Java program code. While the logic code can be mapped from the desgined activity diagram. Evaluation of execution of the Java program shows that the functional features such as Sales Transactions can be executed and used according to the specifications.